Wage determination in Argentina: an econometric analysis with methodology discussion - Galiani, Sebastian (2000)
Micro evidence on the relationship between wages and unemployment has been provided recently in a series of contributions by Blanchflower and Oswald (1994, 1995). They argue for the existence of a wage curve linking local wages to local unemployment. They claim the relationship to be static. They also claim that the unemployment elasticity of pay is -0.1 across-countries. They claim that this shows that countries exhibit the same degree of wage flexibility. In this paper we study wage determination in Argentina. We believe that both regional and national factors affect wage setting. Thus, we also favor the modelization at the regional level of aggregation. However, we show that a regional wage two-way fixed effects error component model does not identify the effect of aggregate variables on wages though it controls for them. Thus, the claim that the estimated unemployment elasticity of pay in this model provides a good measure of wage flexibility may be misleading. We propose a three-step estimator that may identify the whole set of parameters of interest in a wage equation. That is, we propose a statistical procedure that may consistently estimate the coefficients of both local and aggregate variables that affect wage setting. We reject the existence of a static wage curve in favor of a dynamic regional wage equation. Additionally, we tentatively favor an error correction mechanism representation instead of a Phillips curve type representation for the common time series component of the regional wages.